Achieving a Rare Breathing Behavior in a Polycatenated 2 D to 3 D Net through a Pillar‐Ligand Extension Strategy. Issue 3 (11th December 2013) - Zhao, Xiaoliang; Liu, Fuling; Zhang, Liangliang; Sun, Di; Wang, Rongming; Ju, Zhangfeng; Yuan, Daqiang; Sun, Daofeng
Abstract Through a pillar‐ligand extension strategy, a rare breathing behavior in polycatenated 2D→3D nets has been achieved. Three variants exhibit interesting sorption properties that range from non‐breathing to breathing behaviors, which is influenced by the angles between the pillars and the single honeycomb layers. The increase in pillar length does not lead to an increase in polycatenation multiplicity, which is controlled by the length of intralayer tripodal carboxylate. It also does not induce obviously expanded interlayer separations but occupies much more the free voids, and as a consequence, a smaller pore volume is obtained. This suggests that in 2D→3D polycatenated bilayer metal–organic frameworks, the porosity is not always enhanced by increasing the length of the interlayer pillars with the intralayer linker remaining unchanged.